2021
DOI: 10.1177/03635465211002149
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of a Modified Coracoid Tunnel-Free Coracoclavicular Sling Technique With Remnant Preservation for the Treatment of High-Grade Acromioclavicular Joint Separation: A Report of 48 Cases With 2 to 5 Years of Follow-up

Abstract: Background: High-grade acromioclavicular (AC) joint separation injuries (Rockwood type IV or V) are surgically indicated because of complete disruption of the AC and coracoclavicular (CC) ligaments, leading to instability and pain. In surgical techniques that require a suspensory system, coracoid tunnel-related complications are not uncommon. Purpose: To report subjective and objective clinical outcomes and complication rates of a modified coracoid tunnel-free CC sling technique combined with CC ligament remna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The clavicle cerclage and tensioning system described in this case series demonstrated satisfactory results in our cohort of patients. The technique used in this report showed similar if not slightly superior results compared to other techniques described in the literature such as Li et al, which reported a CC distance average of 11.2mm+/-1.8mm at the final follow-up [15]. The follow-up duration in the Li et al study was a mean +/-SD follow-up of 39.3 +/-8.9 months (range, 24.7-36.3 months) while our follow-up period was 3.29 months, highlighting a limitation in our study being its short follow-up duration.…”
Section: Discussionsupporting
confidence: 72%
“…The clavicle cerclage and tensioning system described in this case series demonstrated satisfactory results in our cohort of patients. The technique used in this report showed similar if not slightly superior results compared to other techniques described in the literature such as Li et al, which reported a CC distance average of 11.2mm+/-1.8mm at the final follow-up [15]. The follow-up duration in the Li et al study was a mean +/-SD follow-up of 39.3 +/-8.9 months (range, 24.7-36.3 months) while our follow-up period was 3.29 months, highlighting a limitation in our study being its short follow-up duration.…”
Section: Discussionsupporting
confidence: 72%
“…In a study of coracoclavicular ligament reconstruction in 17 patients conducted by Banffy et al [20], an arti cial material was used to form a ring in the coracoid process for suspension, and satisfactory results were obtained at the 2-year follow-up, with no coracoid fracturs. In a series of 48 cases of coracoclavicular ligament reconstruction conducted conducted by Li et al [21], used coracoid process drill-free suspension xation, only 8.3% of patients had partial (CCD) loss, and no pain, instability, or coracoid fracture-related complications were reported. These evidences suggest that coracoclavicular ligament reconstruction with drill-free suspension xation of the coracoid process can not only achieve good clinical effects but also avoid coracoid fractures, our results are basically consistent with those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%